Heritage, culture and rights : challenging legal discourses - Heritage, culture and rights: challenging legal discourses (Conference) (2013 : University of New South Wales); Durbach, Andrea, 1957-; Lixinski, Lucas; Australian Human Rights Centre (Oxford ; Portland, Oregon : Hart Publishing, an imprint of Bloomsbury Publishing Plc, 2017)
Cultural heritage law and its response to human rights principles and practice has gained renewed prominence on the international agenda. The recent conflicts in Syria and Mali, China's use of shipwreck sites and underwater cultural heritage to make territorial claims, and the cultural identities of nations post-conflict highlight this field as an emerging global focus. In addition, it has become a forum for the configuration and contestation of cultural heritage, rights and the broader politics of international law. The manifestation of tensions between heritage and human rights are explored in this volume, in particular in relation to heritage and rights in collaboration and in conflict, and heritage as a tool for rights advocacy. This volume also explores these issues from a distinctively legal standpoint, considering the extent to which the legal tools of international human rights law facilitate or hinder heritage protection. Covering a range of issues across Africa, Asia, Europe, Latin America and Australia, this volume will be of interest to people working in human rights, heritage studies, cultural heritage management and identity politics around the world. 'This book fills an important gap in the literature on heritage and rights and, in particular, human rights law. With articles from leading experts addressing the legal human rights dimensions of cultural heritage protection, it makes a significant contribution to debates over issues such as 'Why should we safeguard heritage and for whom?' and 'What is the relationship between heritage safeguarding and protecting human rights?'. These are deep questions of profound significance to individuals, communities and even nations around the world and are of increasing urgency today. It critically analyses the relationship between heritage and human rights that can be potentially pernicious as well as mutually reinforcing, placing this analysis within the wider context and with a broad geographical scope with examinations of the heritage/rights relationship in Southeast Asia (Cambodia), China and sub-Saharan Africa.' Dr Janet Blake, Associate Professor in Law, Shahid Beheshti University, Tehran 'Traversing the destruction of mausoleums in Timbuktu to war crimes trial by the International Criminal Court, Heritage, Culture and Rights explores the crucial links between human rights and the protection of cultural heritage. The essays are accessible to all viewing the destruction of cultural heritage as a breach of human dignity and identity. Unputdownable.' Professor Gillian Triggs, President of the Australian Human Rights Commission 'This collection of essays by leading scholars, though primarily Australian in origin, is universal in orientation. Ranging from a broad survey of the applicable laws of armed conflict to a detailed consideration of urban design in Southeast Asia, the essays offer significant insights into the relationship between the protection and use of cultural heritage, on one hand, and fundamental human rights, on the other. Ultimately, the mutual reinforcement of the two disciplines of law prevails over carefully-acknowledged tensions between them. Readers at all levels of expertise will find the book of great interest.' Professor James Nafziger,Thomas B Stoel Professor of Law and Director of International Programs at the Willamette University College of Law
Introduction -- Andrea Durbach and Lucas Lixinski -- Opening the toolbox of international human rights law in the safeguarding of cultural heritage -- Francesco Francioni and Lucas Lixinski -- Culture, rights and the post-2015 development agenda -- Ben Boer -- Cultural heritage, human rights and the privatisation of war -- Ana Vrdoljak -- The urban village and the megaproject : linking vernacular urban heritage and human rights-based development in the emerging megacities of southeast Asia -- Scott Hawken -- Between rights in the city and the right to the city : heritage, character and public participation in urban planning -- Amelia Thorpe -- The tension between rights and cultural heritage protection in China -- Stefan Gruber -- Heritage and human rights : reframing the conservation ethic -- Josephine Gillespie -- The poverty of world heritage management in sub-saharan Africa : the legacy of colonialism and disregard of human rights -- Folarin Shyllo -- Cultural heritage as transformation : a study of four sites from post-apartheid South Africa -- Andrea Durbach -- Heritage listing as self-determination -- Lucas Lixinski -- World heritage, cultural conflicts and political reconciliation -- Andrzej Jakubowski.
"This book grew out of a workshop, Heritage, Culture and Rights: Challenging Discourses, which we convened under the auspices of the Australian Human Rights Centre at the University of New South Wales (UNSW), Sydney and the Association of Critical Heritage Studies, with financial and infrastructure support from UNSW Law and a grant from the Australian National Commission for UNESCO."
Includes bibliographical references and index.
Also issued in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Electronic reproduction.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Cultural property -- Protection -- Law and legislation -- Congresses